A Legal Analysis of Copyright Holders of Digital Music Works in Cases of Piracy Under Law No. 28 of 2014 on Copyright - Nofida Buulolo; Ismayani Ismayani; Taufika Hidayati (SEAN Institute, 2026)
This study examines the legal protection of digital music copyright holders in the context of piracy under Law Number 28 of 2014 concerning Copyright. The main issues studied are how this legal protection is implemented in the ever-evolving digital landscape and what factors contribute to the prevalence of digital music piracy. The research method used is normative legal analysis with a legislative approach and case studies. Data were collected through a literature review, focusing on primary legal materials such as Law Number 28 of 2014 concerning Copyright, Supreme Court decisions, and jurisprudence related to digital music copyright, as well as secondary legal materials such as books and legal journals. The findings indicate that Law Number 28 of 2014 provides comprehensive legal protection for digital music copyright holders, including exclusive rights to publish and reproduce works, as well as economic and moral rights. The factors causing piracy are multidimensional, encompassing technology, socio-cultural aspects, economics, and weaknesses in law enforcement. This study recommends strengthening digital monitoring mechanisms, increasing legal sanctions, and improving public education to create a fair and sustainable digital music ecosystem.